Mitochondrial DNA: a promising tool for characterising the population of the Tiúba stingless bee, Melipona fasciculata (Apidae, Meliponini) - R. N. Sousa; G. G. Santos; S. L. Nogueira; G. C. Fernandes; B. F. S. De Sousa; J. R. S. Barros (Brazilian Journal of Biology)
Abstract The Melipona fasciculata popularly known as Tiúba, is a specie of stingless bee that is distributed in the north of Brazil, over-represented in Maranhão State. This bee is of great importance to stingless bees (SLB) beekeepers, as it produces a large quantity of honey with an excellent taste. The genetic diversity of the Tiúba populations was examined with molecular approach using the mitochondrial DNA (mtDNA) marker. A total of 30 samples from cities in Maranhão State were analysed for the mtDNA intergenic region located between the cytochrome c oxidase I (COI). The molecular analyses identified 8 haplotypes, 3 of which are shared between locations, where the commercialization of beehives is very common and the commercialization of beehives is very common. The populations of Imperatriz and São Bento have the highest diversity indices, and the neutrality tests showed that the populations might be expansion. The fixation index of the study populations showed a high differentiation rate of 0.6218. These Tiúba populations exhibit a high level of genetic structuring, as well as potentially being in a population expansion phase.